PERBEDAAN HASIL BELAJAR DENGAN MENGGUNAKAN STRATEGI PEMANFAATAN PERPUSTAKAAN SEKOLAH SEBAGAI SUMBER BELAJAR SISWA SDN KOTA BENGKULU - Sari, Khamilla Andina; Lusa, Herman; Yusuf, Syahril (UNIB Press, 2017)
The aim of this research is to determine the differences in student learning outcomes by using the school library utilization strategy as learning resources in the civics studies in grade V SD Negeri 82 Kota Bengkulu. This research is a quantitative research. The design of this research was Quasi Experimental Design with design types The Matching Only pretest-posttest control group design, where taking the test twice before and after the treatment in the sample class. Subjects in this research are the students of fifth grade of SDN 82 Kota Bengkulu which consists of the VA class as the experimental class and the VB class as the class control. The research instrument used is forms of test sheet multiple choices given by the pretest (before giving treatment) and posttest (after giving treatment). The data of this study was analyzed by using inferential analysis T-test. The results showed by using t-test tcount 5,64 and ttabel 2,00. So tcount (5,64)> ttabel (2.00). By the result, it can be concluded that there are differences in student learning outcomes by using the school library utilization strategy as learning resources in the civics studies in grade V SD Negeri 82 Kota Bengkulu.